TECHNOLOGICAL INNOVATION AND EDUCATION PORTALS AS TEACHING AND LEARNING EFFECTIVENESS STRATEGIES - Antonius Totok Priyadi; Khairullah; Lisa Sabila (Adisam Publisher, 2025)
This research aims to analyze the role of technological innovation and educational portals as strategies in increasing the effectiveness of teaching and learning in the digital era. The development of information technology has changed the paradigm of education, from a conventional system based on a face-to-face to a more flexible and inclusive digital learning. The education portal is one of the innovations that provides broad access to learning materials, discussion forums, and online evaluations to support a more interactive learning process. The research method used is descriptive qualitative with a literature review approach. Data was obtained from scientific journals, books, and relevant research reports regarding education digitalization, learning portals, and effectiveness. The analysis was carried out thematically to identify the contributions, opportunities, and challenges of implementing the education portal in supporting the teaching and learning process. The study results show that education portals contribute positively to the effectiveness of learning in terms of improving material understanding, learning motivation, and interaction between teachers and students. However, the implementation of education portals still faces obstacles, including limited infrastructure, digital literacy gaps, and the readiness of educators to adopt new technologies. This study concludes that technological innovation through education portals is not just a tool, but an educational transformation strategy that has the potential to improve the quality of learning sustainably. For this reason, policy support, infrastructure, and strengthening the capacity of human resources are needed so that the implementation of education portals can run optimally and evenly.